The Cranfield Ergonomics Laboratory - Singleton, W. T. (College of Aeronautics, 1963)
Ergonomics is a cross discipline between the human sciences and engineering. It is concerned with the design of man/machine systems, using the characteristics of the operator as the frame of reference. The state of our technology is now such that almost any purposeful activity involves a man and a machine operating together. Thus the basic working or fighting unit is the man/machine system and the efficiency of the system is dependent on the weakest link. Until recently this has usually been within the machine, but we have reached the stage when it may now be in the man, or between the man and the machine. It thus becomes necessary for the engineering designer to build his "hardware" to suit the human operator as well as to meet the need which the system is required to fulfil. To achieve this objective the designer requires data and advice on human performance. The provision of this information is a difficult task because of the complexity and variability of human performance. There are, at present, few laws of human behaviour which can take quantitative forms, and to obtain numerical information it is often necessary to resort to direct manipulation of the relevant variables. Fortunately, there is a considerable body of knowledge and experience on the measurement of human performance which has been developed by psychologists, physiologists, anatomists and work study practitioners. Thus, ergonomics is based on statistically controlled experimentation and, in common with other experimental sciences, it can only be taught effectively by a combination of lectures and laboratory periods. The objective of the Cranfield Ergonomics Laboratory is to provide these facilities so that students can acquire a knowledge of experimental techniques and of the variables which they are manipulating. The students may be specialists in this field or may be engineers from other fields who wish to acquire some knowledge of the subject. The formal experiments require at least two students, one to act as a subject and the other as observer. Each experiment takes two or three hours to perform, and a similar period is required to read appropriate reference material and write a report.